A new solid‐state mode of hot corrosion at temperatures below 700°C. Issue 8 (17th June 2019) - Kistler, Emily; Chen, Wei‐Ting; Meier, Gerald H.; Gleeson, Brian
Abstract: Preliminary results on a single‐crystal nickel‐based superalloy indicated that hot corrosion can occur at temperatures as low as 550°C, where liquid formation, generally believed to be responsible for Type II hot corrosion, is not predicted. Additional tests were conducted on pure‐nickel samples at 650°C and below to more clearly elucidate the mechanism of this very low‐temperature hot corrosion. Environments in dry air and O2 ‐(2.5, 10, 100, and 1000) ppm SO2 were studied. Based on the results obtained, a solid‐state corrosion mechanism was inferred. The mechanism relies on the formation of a previously unreported compound phase, which was identified using transmission electron microscope analysis that indicated the stoichiometry of Na2 Ni2 SO5 . Furthermore, it was nanocrystalline in structure and metastable. It was deduced that the Na2 Ni2 SO5 formation was responsible for the rapid nickel transport required for the observed accelerated corrosion process. Moreover, its eventual decomposition resulted in a mixed product of porous NiO with embedded particles of Na2 SO4 . Application of the proposed mechanism to nickel‐based alloys is discussed. Abstract : Sulfate‐deposit‐induced corrosion was found to occur as low as 550°C, where liquid formation is not predicted. Studies were completed on a nickel‐based superalloy and pure nickel in an SO2 ‐containing atmosphere with Na2 SO4 deposit, either as a layer or as isolated crystals. A new solid‐state mode of deposit‐induced corrosion was proposed, which relies on the formation of a nanocrystalline Na–Ni–S–O phase.